The legal framework of UTM for UAS - Ryan, Richard; Al-Rubaye, Saba; Braithwaite, Graham; Panagiotakopoulos, Dimitrios (IEEE, 2020)
It is very apparent that the legal framework for Unmanned aircraft system Traffic Management (UTM) needs to be developed as regulators grapple with issues that relate to legal responsibility and accountability for each UTM stakeholder as the proliferation of drones increases. There is a considerable ‘legal lacuna’ that exists creating much uncertainty within the industry with respect to investment and the direction of innovation. Drones are being utilised today under controlled conditions as technology and ability develops, but with this accelerated pace of technological development, existing regulations soon become limited to address new capabilities and thus become out of date. Policy has become law in many jurisdictions, but policy needs to be developed further to keep pace with demand because safety is paramount. This paper investigates and highlights legal aspects that a regulator and UTM stakeholders have to consider in developing good drone law. It is essential that a properly considered legal framework is developed for many reasons including, but not limited to, increased positive public perception, proliferation of innovation of use cases for Unmanned Aerial Systems, improved environmental impact and improved safety. This paper describes the fundamentals that a well designed and considered legal framework for a UTM system should address, in order to provide much needed certainty that can guide all stakeholders to a regulatory path that leads to safe maximized utility of drones in shared airspace
Keywords: UK Civil Aviation Authority (CAA); European Aviation Safety Authority (EASA); Federal Aviation Administration (FAA); aviation regulation; Drone Law; U-space; Traffic Management (UTM); Unmanned Aerial System (UAS); Unmanned Aircraft System; Unmanned Aerial Vehicle (UAV)